Rectification of surface polaritons in an insulator in a magnetic field at the boundary with a metal - Chupis, I. E.; Mamaluy, D. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
Surface polaritons in a semi-infinite insulator in a constant magnetic field at the boundary with an ideal metal or a superconductor have been considered. These polaritons are induced by dynamic magnetoelectric interaction, which exists in any insulator in the presence of a magnetic field. The modes of these surface polaritons differ appreciably in opposite directions of the magnetic field or the propagation of the wave. As a result polaritons of the given optical or IR frequency propagate only in one direction, which is the effect of rectification of surface electromagnetic waves. The inversion of the magnetic field results in &quotswitching on&quot or &quotswitching off&quot of surface polaritons.